Multi-Turn Refinement Loops Enhance Robustness in Code Generation Models on HumanEval - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 15 peer-reviewed papers addressing the following research question: What is the impact of multi-turn refinement loops on the robustness of code generation models against adversarial prompts in the HumanEval dataset. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.2/10. This report is a machine-generated literature synthesis and does
Machine-generated literature synthesis.